2013
DOI: 10.1038/nature12176
|View full text |Cite
|
Sign up to set email alerts
|

Distinct behavioural and network correlates of two interneuron types in prefrontal cortex

Abstract: Neurons in prefrontal cortex exhibit diverse behavioural correlates1–4, an observation that has been attributed to cell-type diversity. To link identified neuron types with network and behavioural functions, we recorded from the two largest genetically-defined inhibitory interneuron classes, the perisomatically-targeting parvalbumin (Pv) and the dendritically-targeting somatostatin (Som) neurons5–8 in anterior cingulate cortex (ACC) of mice performing a reward foraging task. Here we show that Pv and a subtype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
490
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(524 citation statements)
references
References 47 publications
33
490
0
1
Order By: Relevance
“…In the final phase of the trial, Pinto and Dan (2015) discovered that dmPFC GABA-ergic interneurons exhibited distinct responses depending on whether the outcome was a reward or a punishment, consistent with previous studies (Courtin et al, 2014;Kvitsiani et al, 2013). Once again, PYR neurons behaved heterogeneously while PV neurons nonselectively responded to both reward and punishment.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…In the final phase of the trial, Pinto and Dan (2015) discovered that dmPFC GABA-ergic interneurons exhibited distinct responses depending on whether the outcome was a reward or a punishment, consistent with previous studies (Courtin et al, 2014;Kvitsiani et al, 2013). Once again, PYR neurons behaved heterogeneously while PV neurons nonselectively responded to both reward and punishment.…”
supporting
confidence: 67%
“…A recent study in dmPFC using extracellular electrophysiological recordings showed that PV and SST neurons displayed distinct firing patterns during a reward behavior at relatively slow timescale . Interestingly, Kvitsiani et al (2013) found that at a faster timescale (< 5 ms) significant correlations were present in PV but not in SST neurons. Thus, although Pinto and Dan (2015) observed consistent intra-type tuning curves in GABA-ergic interneurons on long timescales, distinct processing strategies may exist between groups at timescales as yet undetectable by calcium imaging.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…While it is clear that they can be broadly categorized based on expression of calcium binding proteins and neuropeptides (Kubota et al, 1994; Markram et al, 2004), abundant evidence that these “cardinal” interneuron types can be further subdivided into functionally relevant subtypes has been obtained (Kvitsiani et al, 2013; Xu et al, 2013). However, molecular definition of these classes of cortical interneurons and determination of their contributions to cortical function and behavior has been difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological and optogenetic studies have identified neuronal populations activated during foraging behavior, attention, emotion, reward expectancy, skeletomotor and visceromotor activity, and other functions (e.g., refs. [2][3][4][5]. Only a small minority of dACC neurons are pain-related.…”
mentioning
confidence: 99%